Strategies and formulations of freeze-dried tablets for controlled drug delivery - Tran, Phuong H.L.; Lee, Beom Jin; Tran, Thao T.D. (International Journal of Pharmaceutics, 2021)
The freeze-drying process has been particularly attractive for preparing tablets for controlled drug release. Although traditional methods, such as granulation or direct compression methods, have been used in various studies to produce tablets with controlled release, freeze-drying processes have been utilized in certain circumstances due to their distinct advantages. However, overall, further development of these strategies, which started with early studies on orally disintegrating tablets, is still necessary. In this review, the incorporation of different formulations into freeze-dried tablets will be discussed. Moreover, the use of excipients, freeze-drying conditions, formulation reconstitution and tablet structure for optimizing the performance of freeze-dried tablets will be reported, including strategies with nanoformulations and natural materials. Generally, this discussion with potential approaches will benefit further development of freeze-dried tablets containing drugs in the pharmaceutical industry.
Keywords: Drug Delivery Systems; Excipients; Freeze Drying; Solubility; Tablets; Controlled release; Dry emulsion tablet; Freeze-dried tablet; Mucoadhesive tablet; Nanoformulation; Orally disintegrating tablet